Sulfur amino acid utilization by growing steers - C.G. Campbell; G. St Jean; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1995)
Two studies were conducted to evaluate sulfur amino acid requirements of growing steers. In trial 1, six ruminally cannulated steers (352 lb) were used to determine methionine requirements . Treatments were abomasal infusions of 0, 2, 4, 6, 8, or 10 g/day of L-methionine. Steers were fed 5.8 lb of a soyhull and wheat straw based diet. Continuous infusion s of acetate, propionate, and butyrate into the rumen and of dextrose into the abomasum were made to increase energy. Amino acids other than methionine were infused into the abomasum to ensure that they did not limit steer performance. Nitrogen retention increased dramatically as methionine supplementation increased and, in the presence of excess cysteine, predicted a requirement of 4 g/day of supplemental L-methionine. Plasma methionine rose with methionine supplementation and predicted a supplemental methionine requirement of 2 g/day. In trial 2, five ruminally cannulated steers (429 lb) were used to determine how efficiently methionine is converted to cysteine in growing cattle. The experimental procedures were similar to those of trial 1, except steers received a basal supplement of amino acids containing 4 g/day L-methionine (requirement in the presence of excess cysteine established in trial 1) and no cysteine. Treatments consisted of abomasal infusions of 0, 1.62, or 3.25 g/day of L-cysteine or 2 or 4 g/day of additional L-methionine. Nitrogen retention was increased by methionine, but not by cysteine, suggesting that cysteine could supply less than one-half of the total sulfur amino acid requirement (methionine + cysteine) of growing steers.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Methionine; Cysteine; Steers; Requirement; Nitrogen retention